Homens da cana e hospitais do açúcar: uma arquitetura da saúde no Estado Novo Men of the sugarcane fields and their hospitals: the architecture of health under the Estado Novo - Marcia Rocha Monteiro (História, Ciências, Saúde: Manguinhos, 2011)
Aborda a constituição de um patrimônio arquitetônico da saúde para a assistência ao trabalhador da agroindústria açucareira no Brasil, a partir do Estatuto da Lavoura Canavieira (1941), sob a égide do Instituto do Açúcar e do Álcool (IAA) e no âmbito da política do Estado Novo (1937-1945). Esclarece as soluções propostas pelo Instituto, fundamentadas em inquéritos realizados nas usinas de cada estado canavieiro e no sistema médico-hospitalar, de raízes norte-americanas da década de 1940, adotado pela burocracia ilustrada do IAA. Destaca os hospitais centrais de Pernambuco e especialmente de Alagoas, contrários às orientações do Instituto. The article explores the emergence of an architectural heritage in the realm of healthcare assistance for workers in the sugarcane agroindustry in Brazil following enactment of the law known as the Estatuto da Lavoura Canavieira (1941), under the auspices of the Instituto do Açúcar e do Álcool and as part of Estado Novo policies (1937-1945). The institute proposed solutions based on surveys conducted at sugarcane mills in cane-producing states and on the medical and hospital system adopted by the institute's enlightened bureaucracy in the 1940s, which took the U.S. system as its model. Special focus is given to the central hospitals in Pernambuco and especially in Alagoas, which opposed institute guidelines.